PEMBANGUNAN IPTEK DI INDONESIA - Nazwirman Nazwirman (Universitas Bina Sarana Informatika, 2010)
Indonesia development has not fully supported by the potential for both educational excellence, including human resources. Indonesia has not optimally utilize and develop science and technology research. The importance of building science and technology, especially knowledge base society. The mastery of science and technology is a new base for the welfare of a nation. The work done in the knowledge-based society for at least five basic elements of structuring society, entrepreneurship, formation of knowledge, skills and management of natural resources and the environment. This essay to provide knowledge about the development of science and technology also knowledge base society in Indonesia. The research method which used explorative by broaden many information from library, and other the result Keywords: Science, Knowledge-Based Society